The Effect of Product Reviews and Store Ratings on Consumer Buying Interest Through Trust in the Marketplace - Dewi Prasetya Rahayu; Kussudyarsana (Majapahit Journal of Islamic Finance and Management, 2025)
This study investigates the influence of product reviews and store ratings on consumer purchase intention through trust in the marketplace, using a quantitative approach with data from 160 respondents and Structural Equation Modeling (SEM) based on SmartPLS. The results show that product reviews significantly and positively influence purchase intention both directly and through trust, while store ratings also positively impact purchase intention but not through trust. This suggests that product reviews play a more crucial role in building consumer trust than store ratings. However, the study does not explore why product reviews are more influential, nor does it consider moderating factors such as review length, authenticity, or the visual presentation of store profiles. Additionally, the generalizability of the findings is limited, as the study does not specify the marketplace or demographic details of the sample. Future research should incorporate these factors and consider stratified sampling to enhance the understanding of how different consumer groups respond to trust-related signals online.